MODELING OF TOOL DEFORMATION OFFSETTING TO WORKPIECE IN TURNING - Vilor L. ZAKOVOROTNIY; Dinh Tung PHAM; Xuan Chiem NGUYEN (Advanced Engineering Research, 2010)
Mathematical simulation of the elastic deformation offsettings of the cutting tool top and the workpiece in their contact point is considered. Algorithms and results of the identification of the model parameters for the case of linear turning are described.